Folate-Equipped Cationic Liposomes Deliver Anti-MDR1-siRNA to the Tumor and Increase the Efficiency of Chemotherapy - Daniil V. Gladkikh; Aleksandra V. Sen'kova; Ivan V. Chernikov; Tatyana O. Kabilova; Nelly A. Popova; Valery P. Nikolin; Elena V. Shmendel; Mikhail A. Maslov; Valentin V. Vlassov; Marina A. Zenkova; Elena L. Chernolovskaya (MDPI AG, 2021)
In this study, we examined the in vivo toxicity of the liposomes F consisting of 1,26-bis(cholest-5-en-3-yloxycarbonylamino)-7,11,16,20-tetraazahexacosan tetrahydrochloride, lipid-helper 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine and folate lipoconjugate (O-{2-[rac-2,3-di(tetradecyloxy)prop-1-yloxycarbonyl]aminoethyl}-O'-[2-(pteroyl-L-glutam-5-yl)aminoethyl]octadecaethyleneglycol) and investigated the antitumor effect of combined antitumor therapy consisting of MDR1-targeted siMDR/F complexes and conventional polychemotherapy using tumor xenograft initiated in immunodeficient mice. Detailed analysis of acute and chronic toxicity of this liposomal formulation in healthy C57BL/6J mice demonstrated that formulation F and parent formulation L (without folate lipoconjugate) have no acute and chronic toxicity in mice. The study of the biodistribution of siMDR/F lipoplexes in SCID mice with xenograft tumors formed by tumor cells differing in the expression level of folate receptors showed that the accumulation in various types of tumors strongly depends on the abandons of folate receptors in tumor cells and effective accumulation occurs only in tumors formed by cells with the highest FR levels. Investigating the effects of combined therapy including anti-MDR1 siRNA/F complexes and polychemotherapy on a multidrug-resistant KB-8-5 tumor xenograft in SCID mice demonstrated that siMDR/F increases the efficiency of polychemotherapy: the treatment leads to pronounced inhibition of tumor growth, reduced necrosis and inflammation, and stimulates apoptosis in KB-8-5 tumor tissue. At the same time, it does not induce liver toxicity in tumor-bearing mice. These data confirm that folate-containing liposome F mediated the extremely efficient delivery of siRNA in FR-expressing tumors in vivo and ensured the safety and effectiveness of its action.